ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SUBJEK PAJAK DALAM MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KECAMATAN TUREN KABUPATEN MALANG - Nadila Putri Hastiti; Anik Malikah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This research was conducted with the aim of analyzing the factors that influence the subject of taxes in making land and building tax payments in Turen District, Malang Regency. The independent variables are Taxpayer Awareness (X1), Tax Service (X2), Taxpayer Knowledge and Understanding of Taxation (X3), Taxpayer Income (X4), and Tax Sanctions (X5). quantitative and technical multiple linear regression analysis. Data collection was carried out using primary data sources by distributing questionnaires arranged on a five-point Likert scale. The distribution of questionnaires is addressed to taxpayers who have been registered in the DHKP of Turen District. From a population of 58,405            Taxpayers registered with the DHKP, Turen District, using the Slovin formula, the results obtained to be sampled were 618 respondents who met the requirements to be processed. The results showed that the variables of Taxpayer Awareness, Tax Services, Knowledge and Understanding of Taxpayers on Taxation, Taxpayer Income, and Tax Sanctions had a positive and significant effect simultaneously on Tax Subjects in making Land and Building Tax Payments.Keywords: taxpayer awareness, tax services, knowledge and understanding of taxpayers on taxation, taxpayer income, tax sanctions.